The equation is
(x - 2) - 7x = 4x + 68
When x = -7, we have
(-7 - 2) - 7(-7) = 4(-7) + 68
This simplifies to:
-9- (-49) = -28 + 68
-9 + 49 = 40
Thus, we have ,
40 = 40
Hence, since the Left hand side of the equation is equal to the right hand side of the equation, we can say that x = -7 is a solution to the equation (x-2) - 7x = 4x + 68
To check if x = 0 is a solution to the equation, we proceed by inputing the value of x as 0 and see if we obtain same result on the L.H.S and R.H.S
When x = 0, we have
(x - 2) - 7x = 4x + 68
(0 - 2) - 7(0) = 4(0) + 68
-2 - 0 = 0 + 68
This implies that
-2 = 68 ( which is not possible)
Hence, since the L.H.S is not equal to the R.H.S, we an conclude that x = 0 is not a solution to the equation